1987
DOI: 10.1111/j.1600-0560.1987.tb01333.x
|View full text |Cite
|
Sign up to set email alerts
|

T6+ and HLA‐DR+ cell numbers in epidermis of immunosuppressed renal transplant recipients

Abstract: The increased susceptibility of the skin of chronically immunosuppressed individuals to viral infections and sunlight-induced malignancies suggests specific drug-induced, dysfunction of local immune mechanisms within the sun-exposed skin of these individuals. To help understand the effect of immunosuppressive therapy alone in the absence of ultraviolet light on the immune system of skin, biopsies were collected from non-sun-exposed buttock skin of control, healthy volunteers and kidney transplant recipients im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…These results are in agreement with those reported by Sontheimer et al (9), and suggest a major and direct effect of immunosuppressive therapy in the density of epidermal LC. Our findings are in apparent contradiction with those of Kelly's report (12). These authors used a direct immunofluorescence technique to evaluate LC density.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results are in agreement with those reported by Sontheimer et al (9), and suggest a major and direct effect of immunosuppressive therapy in the density of epidermal LC. Our findings are in apparent contradiction with those of Kelly's report (12). These authors used a direct immunofluorescence technique to evaluate LC density.…”
Section: Discussioncontrasting
confidence: 99%
“…They further suggested that the reduction in the number of LC in RTP could explain the high incidence of skin cancer in sun exposed areas observed in these patients (1)(2)(3). More recently, Kelly et al (12), have restudied this topic in non-exposed skin, but they were not able to find any decrease in the number of epidermal LC in RTP compared with normal controls. These results could suggest that immunosuppressive drugs have no direct effect on LC density.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation